Vascular Aging in Rodent Models: Contrasting Mechanisms Driving the Female and Male Vascular Senescence - Barros, Paula R.; Costa, Tiago J.; Akamine, Eliana H.; Tostes, Rita C. (Frontiers in Aging, 2021)
Increasing scientific interest has been directed to sex as a biological and decisive factor on several diseases. Several different mechanisms orchestrate vascular function, as well as vascular dysfunction in cardiovascular and metabolic diseases in males and females. Certain vascular sex differences are present throughout life, while others are more evident before the menopause, suggesting two important and correlated drivers: genetic and hormonal factors. With the increasing life expectancy and aging population, studies on aging-related diseases and aging-related physiological changes have steeply grown and, with them, the use of aging animal models. Mouse and rat models of aging, the most studied laboratory animals in aging research, exhibit sex differences in many systems and physiological functions, as well as sex differences in the aging process and aging-associated cardiovascular changes. In the present review, we introduce the most common aging and senescence-accelerated animal models and emphasize that sex is a biological variable that should be considered in aging studies. Sex differences in the cardiovascular system, with a focus on sex differences in aging-associated vascular alterations (endothelial dysfunction, remodeling and oxidative and inflammatory processes) in these animal models are reviewed and discussed.